Pembuatan Model Geologi Bawah Permukaan dengan Metode Geolistrik Dan Studi Stratigrafi pada Rembesan Gas DiJatilawang, Banyumas - Purwasatriya, Eko Bayu; Waluyo, Gentur (Dinamika Rekayasa, 2011)
Banyumas basin is oneof sedimentary basin inIndonesia whichhasn’t proven yet its economical hydrocarbonreserves, although there are several oil and gas seeps in this area which is indicate mature source rocks had been migrated. One of itsgas seep is located on Karanglewas village, Jatilawang, Banyumas which hadbeen flowing its gases since tens years ago. Geoelectrical method and Stratigraphic studyare the methods usedin this research to built a geological subsurface model of Jatilawang’s gas seep.Geoelectrical method isintent to finding the distribution of gas seep over the area and also to finding the direction of fault structure which can be act asa path for gases to flowing up. Stratigraphic study comprise of lithology description, strike and dip measurement, and study of other secondary geological data. Interpreted subsurfacegeological model showing that sandstone dominated bed of Halang Formation is filled by gases and become gas pockets near the surface. Fault direction also interpreted from correlation of these gas pockets and resulting directionof N 115° E and dip of fault plane is45°.Gas flowing through fault and probably the source comes from gas cap of Jatilawang’s anticline. Predicted location of gas cap is about 610 meters to the south, and depthabout 620 meters.